Implementing circularity measurements in industry 4.0-based manufacturing metrology using MQTT protocol and open CV: a case study - Kamran Latif (Tanjung Malim, 2023)
Implementing circularity measurements in industry 4.0-based manufacturing metrology using MQTT protocol and open CV: a case study by Kamran Latif